O controle das comissões administrativas sobre o critério da autodeclaração dos pretos nas políticas públicas de cotas raciais de acesso ao ensino superior no Nordeste - Pedrosa, Eduarda Shirley Fernandes de Oliveira Vale (Universidade Federal Rural do Semi-Árido, 2021)
The affirmative policies of racial quotas provided for in Law nº 12.711/2012 contributed to the insertion of subjects who declare themselves black in public higher education. The criterion for setting them as blacks is self-declaration. Due to self-recognition fraud, public universities have, in view of the legal and constitutional boundaries, constituted Administrative Commissions of Heteroidentification. Thus, this dissertation aims to investigate the possibilities and limits of administrative control over the criterion of self-declaration of blacks in the policy of racial quotas of access to higher education in the Northeast. In this sense, it develops qualitative, descriptive and explanatory research, with the use of the deductive method. As methodological instruments, the dissertation, divided into four chapters, was used by documentary and bibliographic research. In the first three, the theoretical premises are established from an interdisciplinary literature review, based on the concepts of race and ethnic-racial identity in Brazil, its demographic application, and the application of the legal principle of isonomy in the Federal Constitution of 1988, in federal legislation on affirmative actions in higher education as public policy and in the jurisprudence of the Supreme Federal Court. In addition, it analyzes the rules of institution, functioning and competencies of the Heteroidentification Commissions of northeastern and federal public universities, according to the documentary survey conducted in 2020. Finally, it is concluded that self-declaration and heteroidentification are complementary procedures that ensure the effectiveness of ethnic-racial quotas in universities. The Administrative Committees of Heteroidentification must observe in their performance the constitutional limits (right to self-recognition, contradictory, broad defense and equality) and the sociocultural conceptions of race, promoting, at the same time, the impediment of the usurpation of quotas vacancies and an anti-racist university policy
Keywords: Cotas Raciais; Autodeclaração; Processo Administrativo; Hetoridentificação; Possibilidades e Limites; Racial Quotas; Self-declaration; Administrative Process; Hetoridentification; Possibilities and Limits; CIENCIAS SOCIAIS APLICADAS::DIREITO